Ecologia trófica de quatro espécies de peixes dominantes na área do reservatório da usina hidrelétrica de Balbina, Amazonas, Brasil - Santos, Maria da Conceição Alves dos (Instituto Nacional de Pesquisas da Amazônia - INPA, 2016)
This study aimed to analyze the diet of Agoniates halecinus, Auchenipterichthys longimanus, Bryconops alburnoides and Hemiodus argenteus, four dominant fish species in the reservoir of the Balbina Dam Power Plant, in three habitats (open water, margin and dead wood standings) during wet and dry periods. Our hypothesis was that there would be differences in the diet of species by habitat, due to the difference in structural complexity among them, and seasonal period, due to changes in food supply. The diet was analyzed by the Frequency of Occurrence and Relative Volume methods, combined by the Alimentary Index. Through data sorting analysis (NMDS), the variation in the composition of the diet of each species by habitat type and seasonal period was analyzed. Bryconops alburnoides and A. longimanus were classified as insectivorous and A. halecinus as piscivorous. Hemiodus argenteus was classified as detritivorous, herbivorous or omnivorous, depending on the habitat and period analyzed. Analyses of variance showed that there was higher variation in the diet composition of the species in the wet period. In relation to habitats, A. halecinus and A. longimanus showed greater variation in diet composition in dead wood standings. For H. argenteus on the banks of the reservoir and B. alburnoides the variation between environments was only lightly accentuated. This indicates that the attenuation of the flood pulse by Uatumã river damming did not nullify completely the temporal variation in water level (and probably in the food supply in the reservoir), which was reflected in the change in the diet of some species. These results also suggest that the prevalence of the species of this study in the Balbina hydroelectric reservoir is the result of the abundance of food resources, and that the structure of fish assemblages may be regulated by bottom-up mechanisms.
Keywords: Peixes; Estrutura trófica; UHE Balnina - Amazonas